The Effects of a Universal School-based Mindfulness Intervention on Children in Special Education - Petäjäjärvi, Heidi (fi=Turun yliopisto|en=University of Turku|, 2017)
The objective of the present study was to examine the effects of a universal school-based mindfulness intervention on resilience, cognitive emotion regulation, and rumination for children in special education (n=118) compared with children in standard education (n=1811). The participants were 11¬–17-year-old students of which 52% were girls. The study was a cluster randomized controlled trial with an active control group. The children in the mindfulness group received a standardized school-based mindfulness intervention called Stop & Breathe, and the active control group received a standardized relaxation programme called Relax, for a duration of nine weeks. Both interventions included weekly 45-minute group sessions conducted by an educated facilitator and home practices. The questionnaire data were collected at two measurement points, before and after the nine-week period. The main focus was to test the following hypotheses: Children in special education (1) are less resilient and have a tendency to use more maladaptive emotion regulation strategies than children in standard education, and (2) therefore will benefit more from practicing mindfulness compared with children in standard education. Group comparisons of the effects of the interventions between the two educational groups were conducted using repeated measures analysis of covariance with two between-subject factors (intervention type and educational group). The results indicated that children in special education had less resilience, and that they used more maladaptive emotion regulation strategies than children in standard education. Although there were baseline differences between children in special education and in standard education, the change in the scores between pre- and post-measurement was similar for the two educational groups, except for the measurement of rumination. For children in special education, practicing mindfulness seemed to have a positive effect in preventing rumination compared with the active control group. For children in standard education, there was no such difference between the mindfulness group and active control group. In the light of these findings, it would be important to find new ways of supporting children in special education in other aspects besides academic achievement. Based on the results of this study, it is not prominent that children in special education would benefit from universal mindfulness-based intervention administered in school settings in particular, even though there may be the potential for more substantial improvement. However, there are various limitations in the present study, which may have interfered with the outcome and conclusions made based on this study. In future research, modifying interventions to match the needs of children in special education, and finding ways to motivate participants for individual practice are essential.